ANALISIS TEKNIK PENERJEMAHAN DAN KUALITAS TERJEMAHAN KALIMAT YANG MENGANDUNG UNGKAPAN SATIRE DALAM NOVEL THE 100-YEAR-OLD MAN WHO CLIMBED OUT OF THE WINDOW AND DISSAPEARED - Ambhita Dhyaningrum; Nababan Nababan; Djatmika Djatmika (Universitas Sebelas Maret, 2016)
Satire is a part of language style, a figure of speech used to mock, critize, or ridicule. The language style exists in a novel by Jonas Jonasson, The 100-Year-Old Man who Climbed Out of the Window and Dissapeared. The aims of this research are to find out the complexity of sentences containing satirical expression, types of satirical expression, rhetorical devices in satirical expression, techniques of translation, and the impact of translation techniques to the quality of translation of sentences containing satirical expression in the novel.This research is a translation study with descriptive qualitative method and single embedded case. The data of research are all sentences containing satirical expression and their translation. This research applies document analysis, questioner, and focus group discussion as the data collecting method. This research also applies Spradley’s ethnographic method as the data analysis technique.The construction of sentences containing satirical expression in this research consist of complex sentences (65 cases or 36,72 %), simple sentences (41 cases or 23,16 %), compound sentenses (35 cases or 19,77 %), compound-complex sentences (32 cases or 18,08 %), and minor sentences (4 cases or 2,26 %). The types of satirical expression consist of personal (67 cases or 37,86 %), episodic (62 cases or 35,03 %),) experential (40 cases or 22,60 %), and textual (8 cases or 4,52 %). The most frequent rhetorical devices in the satirical expressions are irony (47 cases or 26,55 %), ridicule (45 cases or 25,42 %), and sarcasm (24 cases or 13,56 %). The translation techniques which has the highest frequency are establihed equivalent (787 cases or 47,30 %), linguistic compression (170 cases or 10,22 %), pure borrowing (130 cases or 7,81 %), transposition (98 cases or 5,89 %), and reduction (92 cases or 5,53 %). The most frequent translation techniques give positive contribution to the whole of translation quality. From the assesment of three aspects of quality, it can be concluded that the translator is capable enough to apply the translation techniques. There is positive impact of the techinques applied and the total quality of translation. The average score of translation quality is 2,82, which can be categorized as high. Keywords: translation, satire, rhetorical devices, translation technique, translation quality.